2023
DOI: 10.1039/d1cs00574j
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of engineered nanomaterial interactions with organ barriers for enhanced drug transport

Abstract: This review discusses the strengths and shortcomings of different strategies to facilitate NP transport across barriers of organs and highlights key findings that can stimulate further advances in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 469 publications
(466 reference statements)
0
3
0
Order By: Relevance
“…It has been widely reported that the presence of PEG shell could decrease the interactions between the biological environment and the PEG-functionalized nanomaterials. The circulation of PEG-modified materials was found to be longer as compared to the nanomaterials without surface functionalization [ 45 47 ]. As a classical surface functionalization approach, DSPE-PEG2000 modification has been widely applied in the decoration of various nanomaterials, enabling their stability and prolong blood circulation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely reported that the presence of PEG shell could decrease the interactions between the biological environment and the PEG-functionalized nanomaterials. The circulation of PEG-modified materials was found to be longer as compared to the nanomaterials without surface functionalization [ 45 47 ]. As a classical surface functionalization approach, DSPE-PEG2000 modification has been widely applied in the decoration of various nanomaterials, enabling their stability and prolong blood circulation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Liver fibrosis is one of the global health problems due to its high prevalence worldwide; in addition, the curative treatments available are very limited (Peng et al 2021;Devarbhavi et al 2023). Liver fibrosis results from the chronic damage to the liver along with the accumulation of extracellular cell matrix (ECM) proteins, which is characteristic of most chronic liver diseases (Lenders et al 2023). The fibrotic liver is characterized by the activation and proliferation of hepatic stellate cells (HSCs), which result in the excessive ECM accumulation and loss of endothelial fenestra and microvilli.…”
Section: Introductionmentioning
confidence: 99%
“…The blood–brain barrier (BBB) as the major physiological and physical barrier in the CNS prevents the vast majority of drugs from entering the brain. , Therefore, how to efficiently cross the BBB and deliver R848 and chemotherapeutic agents to TAMs and GBM cells specifically is a key challenge. , By taking advantage of inherent transport mechanisms of the BBB, a plethora of conventional brain-targeting drug delivery systems have been developed to overcome the BBB and assist the delivery of drugs to the brain parenchyma. Among them, receptor-mediated transcytosis (RMT) represents the most popular mechanism given that various receptors are expressed on the BBB endothelium, including low density lipoprotein receptor (LDLR) family members, transferrin receptors, insulin receptors, melanin transferrin, etc. , Specifically, LDLR-related protein 1 (LRP1) is one of the most promising receptors due to abundant expression on both BBB endothelium and GBM cells . Nanoparticles (NPs) modified with a LRP1 recognizing ligand not only could effectively target the BBB but also could target GBM cells after crossing BBB …”
mentioning
confidence: 99%